Multiphoton absorption and graphitization in poly(methyl methacrylate)-coated aluminum nanoantenna arrays - Hobbs, Richard (My University, 2020)
Collective electron oscillations, termed surface plasmons, in subwavelength metallic nanostructures can be excited by light, giving rise to an enhanced optical near-field at the surface of the metal. This field enhancement decays with distance away from the surface of the metal while the surface plasmon can decay due to energy transfer to the metal and surrounding materials. This energy transfer, previously considered detrimental for applications in photonics, shows promise for photocatalysis and energy conversion by exploiting the enhanced light-matter interactions present in plasmonic materials. However, insight into the chemical mechanism of energy transfer within the optical near-field is relatively elusive. Here we propose a method to investigate plasmon-driven chemical transformations in poly(methyl methacrylate) (PMMA) using aluminium nanostructures having surface plasmon modes that are resonant with laser illumination at 𝜆 = 532 nm. Surface-plasmon-driven chemical changes in PMMA were observed by Raman spectroscopy. Specifically, graphitic carbon was observed to form on plasmonic nanostructures. The volume of exposed PMMA was observed to scale with the second power of the laser intensity, which is consistent with a two-photon absorption process. This observation suggests that two-photon absorption drives polymer-chain scission, resulting in the transformation of PMMA into graphitic carbon.
PUBLISHED
Keywords: Nanoscience & Materials; Nanostructures; Nanotechnology; Optical materials; Spectroscopy; Surface chemistry